Utilizing the Foundation Course Period for Sensitizing Medical Graduates about Writing Rational Prescriptions - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Journal of Integrated Health Sciences)
It won't be wrong to say that patients trust their doctors that they can cure them of their illnesses and will take steps to ensure their well-being, with majority of them not being aware about the impact of a pharmaceutical industry on medical practice. The attitude of a medical professional towards the pharmaceutical industry can form quite early in their medical training, keeping the fact that they are exposed to an informal curriculum from their teachers or even peers. The students have to be sensitized about all this throughout their medical under-graduation period and the best place to initiate this in the Foundation Course itself. Similar things can be dealt again as a part of the Early Clinical Exposure sessions, AETCOM sessions, during clinical postings and during the internship. In conclusion, in order to stop the practice of irrational prescriptions, the undergraduate students should be trained to deal with the pharmaceutical industries within their curriculum across the entire duration, so that they are empowered enough to not get unduly influenced by the industry.